Diagnostic value of monocyte chemoattractant Protein-1, soluble mannose receptor, Presepsin, and Procalcitonin in critically ill children admitted with suspected sepsis - Noha A. Hassuna; Ebtesam Elgezawy; Suzan O. Mousa; Reem A. AbdelAziz; Reham A. Ibrahem; Wafaa Yousif Abdel Wahed; Khalid A. Nasif; Enas M. Hefzy (BMC, 2021)
Abstract Introduction The differentiation between systemic inflammatory response syndrome and sepsis is very important as it determines essential treatment decisions, such as selection, initiation, and duration of antibiotic therapy. Objectives We aimed to investigate the diagnostic value of Procalcitonin, Monocyte Chemoattractant Protein-1, soluble Mannose Receptor, Presepsin as early biomarkers of pediatric sepsis in comparison to systemic inflammatory response syndrome in severely ill children. Patients and methods This study included 58 children diagnosed as sepsis (group 1), 24 children with systemic inflammatory response syndrome without infection (group 2), and 50 healthy children as controls (group 3). All the plasma levels of the studied biomarkers were measured and ROC curves were created for all the tested parameters to discriminate between sepsis and SIRS. Results The area under the curve for Monocyte Chemoattractant Protein-1 was 0.926 (0.846-0.927) with sensitivity 100% and specificity 62.5%. The soluble Mannose Receptor had the highest sensitivity (100%), with AUC equals 1(.0.956-1.0) and specificity of 100%. The cut-off values for Procalcitonin, Presepsin, soluble Mannose Receptor, and Monocyte Chemoattractant Protein-1 and were: 0.62 ng/ml, 100 pg/ml, 13 ng/ml and 90 pg/ml, respectively. In septic cases, both soluble Mannose Receptor and Procalcitonin have positive correlations with the severity of sepsis, low Glasgow Coma Scale, ventilatory support, use of inotropic drugs and mortality rate (r = 0.950, 0.812, 0.795, 0.732 and 0.861respectively) for soluble Mannose Receptor and (0.536, 0.473, 0.422, 0.305 and 0.474 respectively) for Procalcitonin. Conclusion Soluble Mannose Receptor, Presepsin, and Monocyte Chemoattractant Protein-1 can be used to differentiate between sepsis and SIRS in critically ill children.